Recent Advances in Metallic Nanostructures-assisted Biosensors for Medical Diagnosis and Therapy - Tiryaki, Ecem; Zorlu, Tolga (Current Topics in Medicinal Chemistry, 2024)
The field of nanotechnology has witnessed remarkable progress in recent years, particularly in its application to medical diagnosis and therapy. Metallic nanostructures-assisted biosensors have emerged as a powerful and versatile platform, offering unprecedented opportunities for sensitive, specific, and minimally invasive diagnostic techniques, as well as innovative therapeutic interventions. These biosensors exploit the molecular interactions occurring between biomolecules, such as antibodies, enzymes, aptamers, or nucleic acids, and metallic surfaces to induce observable alterations in multiple physical attributes, encompassing electrical, optical, colorimetric, and electrochemical signals. These interactions yield measurable data concerning the existence and concentration of particular biomolecules. The inherent characteristics of metal nanostructures, such as conductivity, plasmon resonance, and catalytic activity, serve to amplify both sensitivity and specificity in these biosensors. This review provides an in-depth exploration of the latest advancements in metallic nanostructures-assisted biosensors, highlighting their transformative impact on medical science and envisioning their potential in shaping the future of personalized healthcare.
Keywords: Diagnostic